Understanding Spatial Determinants of Urban Mobility in Makassar through Geographic Weighted Regression - Irwan, Irwan; Anugrah Yanti, Suci; Akil, Arifuddin (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
Urban mobility patterns are influenced by a complex interplay of factors, including land use, population density, and socioeconomic conditions. This study aims to examine the spatial determinants of urban mobility in Makassar City, Indonesia, to guide targeted transportation and urban planning policies, using Geographically Weighted Regression (GWR). GWR is employed to account for spatial heterogeneity, as it captures localized variations in relationships unlike global regression models. The analysis incorporates travel time, travel cost, land use, population, and poverty data. Results indicate that the relationships between these variables vary significantly across different parts of the city. Land use, particularly the mix of residential, commercial, and industrial areas, emerges as a critical factor influencing travel patterns. Population density and poverty levels also shape mobility behaviors. The findings highlight the need for spatially targeted transportation policies and urban planning strategies to address the diverse mobility needs of Makassar's residents